DO THE MATERIAL PROPERTIES OF CUTLERY AFFECT THE PERCEPTION OF THE FOOD YOU EAT? AN EXPLORATORY STUDY - Piqueras-Fiszman, B; Spence, C (2011)
Our perception of food depends both on the contextual conditions in which it is presented and on the way the food is consumed; hence, the current trend toward investigating these contextual variables in empirical research. In most meal situations, people interact with the food that they consume by means of a variety of accessories, such as dishes and cutlery that fulfill the consumers' functional requirements. However, despite the important role that these accessory stimuli play during the consumption of food, little research has been carried out in order to investigate how they may affect food perception. The present preliminary study was therefore undertaken in order to explore how the cutlery, specifically two teaspoons (a plastic one with metallic finish and a stainless steel one), affected consumers' sensory and hedonic perception of yoghurt. Consumers' quality and liking judgments concerning identical yoghurt samples differed significantly when tasted either with a metallic plastic spoon or else with a stainless steel spoon, the latter resulting in significantly higher scores. PRACTICAL APPLICATIONS: These results contribute to our knowledge of how contextual variables affect a consumer's perception of food. These findings open up new research directions emphasizing the potential importance of the properties of cutlery and its influence on consumers' perception of food. These results are relevant to product development and to caterers and restaurateurs because different dishes (i.e., foodstuffs/flavors) could be matched with different types of cutlery in order to increase convenience and, at the same, time potentially enhance the consumers' eating experience. © 2011 Wiley Periodicals, Inc.